Freeheld [videorecording (DVD)] - Moore, Julianne; Page, Elliot, 1987-; Carell, Steve, 1962-; Wade, Cynthia (Cynthia Leigh) (Lionsgate, 2016)
When a New Jersey police lieutenant is diagnosed with terminal cancer, she and her registered domestic partner must work to secure her pension benefits.